The Relationship between Training and Career Development and Job Satisfaction of the National Police (Polri) at the NTT Regional Police - Novi Indah Earlyanti; Agung Kusprabandaru (Transpublika Publisher, 2026)
Job satisfaction among members of the Indonesian National Police (Polri) is an important issue in human resource management in the public sector, particularly in efforts to improve professionalism, performance, and quality of service to the community. Various organisational efforts such as training and career development are considered important strategies for improving the competence, capabilities, and motivation of members, which ultimately can affect their level of job satisfaction. Therefore, this study aims to analyse the relationship between training and career development on the job satisfaction of members of the Indonesian National Police (Polri) in the East Nusa Tenggara (NTT) Regional Police. This study uses a quantitative approach with multiple linear regression analysis. The research sample consisted of 321 Polri members in the NTT Regional Police, selected using simple random sampling. Data collection was conducted through a questionnaire with a 7-point Likert scale distributed via social media. The data was then analysed using SPSS software by looking at the significance value, t-test, and F-test. The results showed that training and career development had a positive and significant relationship with the job satisfaction of Polri members in the NTT Regional Police. These findings indicate that improving the quality of relevant training and establishing a clear and structured career development system can increase the job satisfaction of police officers. Thus, effective training and planned career development play an important role in increasing the job satisfaction of Polri members, which in turn can support the improvement of professionalism, performance, and effectiveness of the police organisation.